Chemical Composition and Biological Activities of the Essential Oil of Athanasia browniiHochr. (Asteraceae) Endemic to Madagascar. Issue 10 (16th October 2013) - Rasoanaivo, Philippe; Fortuné Randriana, Richard; Maggi, Filippo; Nicoletti, Marcello; Quassinti, Luana; Bramucci, Massimo; Lupidi, Giulio; Petrelli, Dezemona; Vitali, Luca A.; Papa, Fabrizio; Vittori, Sauro
Abstract The essential oil obtained from hydrodistillation of flowering aerial parts of Athanasia brownii (Asteraceae) was studied for its chemical composition by GC/FID and GC/MS, and for biological activity, namely, antioxidant, antimicrobial, and chemopreventive potential, by DPPH (=2, 2‐diphenyl‐1‐picrylhydrazyl), ABTS (=2, 2′‐azinobis[3‐ethylbenzothioline‐6‐sulfonic acid), and FRAP (=ferric reducing antioxidant power), disk diffusion test, and MTT (=3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide) assay, respectively. The oil was characterized by a high content of oxygenated sesquiterpenes (71.2%), with selin‐11‐en‐4α‐ol (24.6%), caryophyllene oxide (8.7%), humulene epoxide II (5.1%), and (E)‐nerolidol (4.9%) as the predominant compounds. The oil showed a moderate activity against streptococci as well as radical‐scavenging potential, while the inhibitory effects against human cancer cells examined such as A375 (malignant melanoma) and HCT 116 (colon carcinoma) were significant, with IC50 values of 19.85 and 29.53 μg/ml, respectively.